Hubungan kejadian tindakan tidak aman (unsafe action) dengan penerapan program Behavior Based Safety (BBS) pekerja - Laisa Maharani (Poltekkes Kemenkes Aceh, 2024)
Background: Behavior Based Safety (BBS) is an effective tool to reduce work accidents. A proactive approach that focuses on At Risk Behavior is a prevention effort through Unsafe Action behavior that is likely to cause work accidents. The implementation of the Behavior Based Safety (BBS) program affects the high behavior of Unsafe Action.Purpose: The study aims to determine the relationship of Unsafe Action with the implementation of the Behavior Based Safety (BBS) program in the engineering department of PT Bernofarm.Methods: Quantitative research using Cross Sectional research methods. The population of this study were 58 people. Determination using purposive random sampling so that the research sample was 50 people. The research was conducted in May-June 2024 in the engineering department of PT Bernofarm. Data collection techniques using a questionnaire. Data analysis using the Chi-Square test.Results: The results show that the Behavior Based Safety (BBS) program in the engineering department of PT Bernofarm has been implemented. However, the lack of maximum application can lead to worker behavior Unsafe Action Events. The proportion of unsafe actions is high in the implementation of the Behavior Based Safety (BBS) program is low, the proportion of unsafe actions is high in the implementation of the Behavior Based Safety (BBS) program is high, while the occurrence of unsafe actions is low in the implementation of the Behavior Based Safety (BBS) program is low. Sig value. 0,000 <0,05, which means that there is a relationship between unsafe actions and the implementation of the Behavior Based Safety (BBS) program for PT Bernofarm workers.Conclusion: there is a relationship between Unsafe Action incidents and the implementation of the Behavior Based Safety (BBS) program in the engineering department of PT. Bernofarm. KeywordsUnsafe Action, Behavior-Based Safety, Worker, Unsafe Action